2015
DOI: 10.1586/14737167.2015.1051037
|View full text |Cite
|
Sign up to set email alerts
|

The cost–effectiveness of diagnostic cardiac imaging for stable coronary artery disease

Abstract: Early and accurate diagnosis of stable coronary artery disease (CAD) is crucial to reduce morbidity, mortality and healthcare costs. This critical appraisal of health-economic literature concerning non-invasive diagnostic cardiac imaging aims to summarize current approaches to economic evaluation of diagnostic cardiac imaging and associated procedural risks, inform cardiologists how to use economic analyses for decision-making, highlight areas where new information could strengthen the economic evaluation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…SPECT and CMR were generally more expensive than CTCA and associated charges showed the highest variability, even when adjusted for PPP. As previously reported [8, 28, 29] such variability, beyond modelling approaches and assumptions, may have significantly impacted on results. As an additional limitation, the health economic evaluation was performed using charges and these often do not reflect real costs.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…SPECT and CMR were generally more expensive than CTCA and associated charges showed the highest variability, even when adjusted for PPP. As previously reported [8, 28, 29] such variability, beyond modelling approaches and assumptions, may have significantly impacted on results. As an additional limitation, the health economic evaluation was performed using charges and these often do not reflect real costs.…”
Section: Discussionmentioning
confidence: 94%
“…In summary, in patients with suspected stable CAD and low-to-intermediate prevalence of obstructive disease, one modality or strategy did not consistently emerge as superior to all others from a health economics perspective [7, 28].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have suggested that CTCA appears to be a cost-effective strategy among patients with suspected CAD, whereas among symptomatic revascularized patients, stress-CMR is more cost-effective than CTCA (68)(69)(70). Cost-effectiveness analyses can hardly be extrapolated to different regions or countries, not only given the different diagnostic algorithm strategies used by local cardiologists, but also the substantially different costs of each technique (71).…”
Section: Clinical Perspectives and Conclusionmentioning
confidence: 99%
“…1 This leads to an increased number of invasive or noninvasive investigations with the primary aim to identify or dismiss the existence of flow-limiting coronary artery disease (CAD). [2][3][4] This results in a continuous resource-consuming problem for healthcare providers worldwide, given the fact that CAD continues to represent the most frequent cause of health-related deaths in the European Union (EU) 5 and contributes to a consistent decrease in the quality of life. 6,7 In the setting of such extensive charges, the accuracy of CAD diagnosis remains of great importance for the management of these patients.…”
Section: Introductionmentioning
confidence: 99%